1990
DOI: 10.1002/jsfa.2740530202
|View full text |Cite
|
Sign up to set email alerts
|

Air classification of bean flour—effects on protein, antinutritional factors and the effect of a fines fraction on cultured explants of small intestinal mucosa

Abstract: Common beans (Phaseolus vulgarisL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This indicated that TIA was concentrated in the protein fraction during air classification, which is expected since trypsin inhibitors are low molecular weight proteins (Chavan & Kadam, ). The coarse fraction, in general, contains lower levels of TIA (mean of 1.61 mg/g dry sample) compared with the pea flour (2.9 mg/g dry sample), confirming the findings of Van der Poel, Arts, and Kik ().…”
Section: Resultssupporting
confidence: 80%
“…This indicated that TIA was concentrated in the protein fraction during air classification, which is expected since trypsin inhibitors are low molecular weight proteins (Chavan & Kadam, ). The coarse fraction, in general, contains lower levels of TIA (mean of 1.61 mg/g dry sample) compared with the pea flour (2.9 mg/g dry sample), confirming the findings of Van der Poel, Arts, and Kik ().…”
Section: Resultssupporting
confidence: 80%
“…This effect is caused by the increase in the protein content, which stabilises the colloid system and by the increase of the oil content, resulting in a decreased particle density. 23 Cooking and popping increased the flour dispersibility. Popped flours showed a maximum value of dispersibility (10.0 cm 3 ) for both species.…”
Section: Flour Dispersibilitymentioning
confidence: 99%
“…Van der Poel et al 23 found that the HPF fraction of bean flour had a higher content of phenolic compounds (average 6.6 g kg −1 ) compared with raw beans (3.6 g kg −1 ). We found that thermal treatments and germination decreased the contents of phenolic compounds in both species.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…A common method to achieve a meat-like structure in the production of meat analogs is extrusion cooking, i.e., the texturization of plant protein extracts. The extraction of plant proteins has been shown to accumulate phytate, a potent inhibitor of iron absorption, as well as other antinutritional components, in the protein-rich fraction later used for extrusion cooking [ 9 , 10 , 11 , 12 ]. During extrusion cooking, high pressure and high temperature are used to reshape the protein structures.…”
Section: Introductionmentioning
confidence: 99%